(untitled) (Research, Society and Development, 2022)
This research aimed to evaluate the nutritional status and the perception of the body image of patients with mental disorders, verifying the relationship between the use of psychotropic drugs and the nutritional profile. It is an exploratory cross-sectional study in a psychiatric clinic hospital in Northeast Brazil. The questionnaire developed for this research was used, with validated questions, organized into five sections: (1) sociodemographic data, (2) questions about the disease, (3) body weight history, (4) anthropometric measurements data, and (5) body image. We used the silhouette scale validated in Brazil to assess body image, and for nutritional status, we collected weight, height, and waist circumference in all participants. Descriptive statistical analysis and the chi-square test were used, adopting a significance level of 5%. A total of 120 patients participated in the study: 70.8% were hospitalized, and 63.3% were male. The results showed an association between the use of psychotropic drugs and variables related to weight and the presence of arterial hypertension. After starting treatment, 86.4% of the participants using antidepressants said they had gained weight involuntarily. Body image distortion and great body dissatisfaction were found, especially in the overweight group. It was concluded that the use of psychotropic drugs was related to outcomes related to weight, and the nutritional profile of overweight was associated with dissatisfaction and distortion of body self-image.